Regulatory Impact Analysis Practice in New Zealand in the Light of Models of Evaluation Use – Inspiration for the Polish Government - Tomasz Kupiec (Management and Business Administration. Central Europe, 2015)
Purpose: The paper describes the functioning of the RIA system in New Zealand using the analogy of RIA and the evaluation of public interventions. Presented solutions can provide nspiration for the Polish government in the process of improving the quality and extent of the use of RIA. Methodology: The analysis is based on a review of government documents and literature, as well as individual interviews and correspondence with representatives of the government of NZ. Conclusions: The RIA system in NZ is not error-free and its shortcomings include inter alia the lack of solutions with respect to ex-post analysis and insufficiently rigorous methodological approach. At the same time, a number of solutions can be regarded as good practice, e.g.: regular external quality reviews of RIS, obligation to supplement each RIS with ‘quality assessment’ and a ‘disclosure statement’ outlining their credibility and utility. Practical implications: The presented strengths of the RIA system in NZ may serve as an inspiration for modifying the RIA system in Poland. Originality: The RIA system is presented through the prism of the model of evaluation use, which is a related tool of collecting information about non-regulatory interventions.